Boundary Value Problems for Fractional Differential Equations with Fractional Multiterm Integral Conditions. (11th May 2014) - Tariboon, Jessada; Ntouyas, Sotiris K.; Singubol, Arisa
Abstract : We discuss the existence and uniqueness of solutions for boundary value problems involving multiterm fractional integral boundary conditions. Our study relies on standard fixed point theorems. Illustrative examples are also presented.